The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/jac/dkv336
|View full text |Cite
|
Sign up to set email alerts
|

Educating healthcare professionals in antimicrobial stewardship: can online-learning solutions help?: Table 1.

Abstract: Education is widely recognized as one of the cornerstones of successful antimicrobial stewardship programmes. There is evidence of important knowledge flaws around antimicrobial prescribing among both medical students and clinicians. Educational interventions improve antimicrobial prescribing, but traditional tools may be insufficient to deliver training to meet the complex demands of global healthcare professionals working across a diverse range of healthcare and resource settings. The educational solutions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 17 publications
1
34
0
1
Order By: Relevance
“…In addition, specific massive open online courses on ABS are globally available now. Although accessibility (internet, non-English speakers) may be an issue in some LMICs and their effectiveness and sustainability still needs to be established, this kind of learning offers great opportunities [61].…”
Section: Stewardship Interventions At the Facility Levelmentioning
confidence: 99%
“…In addition, specific massive open online courses on ABS are globally available now. Although accessibility (internet, non-English speakers) may be an issue in some LMICs and their effectiveness and sustainability still needs to be established, this kind of learning offers great opportunities [61].…”
Section: Stewardship Interventions At the Facility Levelmentioning
confidence: 99%
“…Many states and hospitals provide online antimicrobial stewardship toolkits with educational material that can be used, for example, the California Department of Public Health (http://www.cdph .ca.gov/programs/hai/Pages/AntimicrobialStewardshipProgramInitiative.aspx) and Nebraska Medicine (Omaha, NE). Massive online open courses (MOOC) and e-learning tools may also be part of the solution (166). One example is the largely publicized MOOC "Antimicrobial Stewardship: Managing Antibiotic Resistance" (http://www .dundee.ac.uk/study/short/antimicrobial-stewardship/) offered by the University of Dundee (Dundee, United Kingdom) and the British Society of Antimicrobial Chemotherapy (Birmingham, United Kingdom).…”
Section: Provider Education: How To Tie the Knotsmentioning
confidence: 99%
“…Educational solutions increasingly need to be timely, efficient, pragmatic, high quality, and aligned to the needs of the professional in a specific context, sustainable, and cost-effective (21). Katherine Barsness and colleagues identified that medical education must address all potential cognitive and technical performance gaps, professionalism, and personal behaviors, as well as effective team communication (22).…”
Section: Discussionmentioning
confidence: 99%